Comparative Plastomes and Phylogenetic Analysis of Cleistogenes and Closely Related Genera (Poaceae) - Wang, Rong; Liu, Kuan; Zhang, Xue-Jie; Chen, Wen-Li; Qu, Xiao-Jian; Fan, Shou-Jin (Frontiers in Plant Science, 2021)
Cleistogenes (Orininae, Cynodonteae, Chloridoideae, Poaceae) is an ecologically important genus. The phylogenetic placement of Cleistogenes and phylogenetic relationships among Cleistogenes taxa remain controversial for a long time. To resolve the intra- and inter-generic relationships of Cleistogenes, the plastomes of 12 Cleistogenes taxa (including 8 species and 4 varieties), one Orinus species, 15 Triodia species, two Tripogon species, and two Aeluropus species were included in the present study. All the taxa showed a similar pattern in plastome structure, gene order, gene content, and IR boundaries. The number of simple sequence repeats ranged from 145 (O. kokonorica) to 161 (T. plurinervata and T. schinzii). Moreover, 1,687 repeats were identified in these taxa, including 1,012 forward, 650 palindromic, 24 reverse, and one complement. Codon usage analysis revealed that these plastomes contained 16,633 (T. stipoides) to 16,678 (T. tomentosa) codons. Sequence divergence analysis among Cleistogenes and closely related genera identified five non-coding regions (trnS-UGA-psbZ, rpl32-trnL-UAG, trnQ-UUG-psbK, trnD-GUC-psbM, trnT-GGU-trnE-UUC). Phylogenetic analysis of complete plastomes indicated that Cleistogenes is sister to a clade composed of Orinus and Triodia, whereas it did not support the sister relationship between the recently proposed subtribe Orininae (Cleistogenes and Orinus) and Triodia. The subtribe Orininae was not supported by our complete plastome data. The split between Cleistogenes and Orinus-Triodia clade go back to 14.01 Ma. Besides, our findings suggested that C. squarrosa and C. songorica are the successive early-diverging groups in the phylogenetic analysis. The other 10 taxa are divided into two groups: a monophyletic group composed of Cleistogenes sp. nov. and C. caespitosa var. ramosa is sister to other eight Cleistogenes taxa. Cleistogenes was estimated to have experienced rapid divergence within a short period, which could be a major obstacle in resolving phylogenetic relationships within Cleistogenes. Collectively, our results provided valuable insights into the phylogenetic study of grass species.